2021
DOI: 10.3390/ijerph182010767
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care COVID-19 Antigen Testing in Exposed German Healthcare Workers—A Cost Model

Abstract: Background: Hospital staffing shortages are again (mid-year 2021) becoming a significant problem as the number of positive COVID-19 cases continues to increase worldwide. Objective: To assess the costs of sending HCW into quarantine (Scenario 1) from the hospital’s and the taxpayer’s perspective versus the costs arising from implementing point-of-care COVID-19 antigen testing (POCT) for those staff members who, despite learning that they have been exposed to hospital patients later found to be infected with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The rate of positive PCR in this study varied between 1.1% and 7.1%. Considering these values, it seems likely that a point of care (PoC) test followed by a PCR is more efficient for screening asymptomatic HW [ 27 ]. How the Omicron variant might change this perspective remains to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of positive PCR in this study varied between 1.1% and 7.1%. Considering these values, it seems likely that a point of care (PoC) test followed by a PCR is more efficient for screening asymptomatic HW [ 27 ]. How the Omicron variant might change this perspective remains to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…The articles researching willingness and preparedness of health professionals during the COVID-19 pandemic correspond to a wide array of geographical contexts, given the worldwide reach of this threat: Palestine [ 32 ], Australia [ 33 , 105 ], Saudi Arabia [ 95 ], China [ 58 , 73 , 74 , 97 , 106 ], Ethiopia [ 37 , 107 ], Bangladesh [ 38 ], Spain [ 32 ], South Korea [ 43 , 47 ], Germany [ 46 , 108 ], Nepal [ 84 , 99 ], Qatar [ 82 ], Canada [ 42 ], Jordan [ 35 , 36 ], and Singapore [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two additional studies, excluded from our pooled analysis because they lacked clinical performance data deserve to be briefly mentioned. Deil et al carried out a preliminary analysis by constructing a mathematical model for estimating the economical burden of sample-and-stay strategy in German healthcare workers based on the use of Quidel Sofia SARS Ag FIA, and concluded that sequential testing was effective to significantly lower the cumulative hospital expenditure due to shortage of quarantined hospital staff [ 43 ]. In a subsequent investigation, the same authors explored the economic impact of using the Quidel Sofia SARS Ag FIA compared to that based on clinical judgement and NAAT for diagnosing COVID-19 in a cohort of German adult patients presenting to the emergency department, concluding that the RDT-AG test enabled to substantially reduce hospital costs by over 200 € for each patient tested [ 44 ].…”
Section: Discussionmentioning
confidence: 99%